Mediating Role of Competitive Strategy and Marketing Capability on The Relationship between EntrepreneurialOrientation and Market Performance - Yanuarti, Dewi Wahyu; Murwatiningsih, Murwatiningsih (Universitas Negeri Semarang, 2019)
The purpose of this research is to analyze the influence of entrepreneurial orientation and competitive strategy to market capability and market performance in kapok mattress industry. So, this results can be used as a consideration for kapok mattress industry and the future research. Populations of this research are 157 owner of kapok mattress industry. The samples of this research are about 130 respondents and this research use questionnaries and documentations for collecting the research data. Data analysis in this research is using Structural Equation Modeling (SEM) method through IBM SPSS AMOS 22 program. The finding of this research show that entrepreneurial orientation affect marketing performance, competitive strategy affect marketing capability, entrepreneurial orientation affect marketing performance through competitive strategy, and entrepreneurial orientation affect marketing performance through marketing capability. In this research, we can conclude that the kapok mattress industry in Pati can increase the marketing performance by increasing entrepreneurial orientation, competitive strategy, and marketing capability. Moreover, this entrepreneurial orientation and competitive strategy in this research can be used in kapok mattress industry properly. For the future research, the other variables can be reviewed for the future research so the kapok mattress industry can find the other marketing strategy for increasing their marketing performance.